Gut microbiome and metabolome remodeling by Wuwei Jianpi San enhances growth and immunity in yaks: a multi-omics approach - Kang, Jianguo; Niu, Chun; Zhou, Ke; Yang, Xue; Hua, Yongli; Wei, Yanming; Ji, Peng; Zhang, Li; Kong, Xiangying; Che, Haizhong (Frontiers in Animal Science, 2025)
BackgroundIntensive yak farming enhances reproductive rates. However, it leads to dietary and sunlight deficiencies, which adversely affect growth and immunity in yaks. This 90-day randomized controlled trial (n=32) systematically evaluated the effects of Wuwei Jianpi San (WJPS), a traditional Chinese herbal formulation, on growth performance, immune function, gut microbiota, and bile acid metabolism in yaks, which is the first systematic association between the traditional Chinese medicine compound WJPS and the multi omics characteristics of yak intestines, aiming to address these challenges.ResultsWJPS supplementation elicited profound phenotypic improvements, including increased in average daily gain (ADG) and a reduction in feed conversion ratio (FCR)(P<0.05), alongside systemic immunomodulation manifested as elevation in lymphocyte count, upregulation of serum IgG(P<0.05), and enhancement of glutathione peroxidase (GSH-Px) activity (P<0.05), without compromising intestinal morphological integrity. Multi-omics analyses unveiled a tripartite mechanism driving these effects. Gut Microbiome Remodeling: WJPS fostered a beneficial microbial ecosystem, significantly enriching commensal taxa such as Ruminococcus and Bacteroides, while suppressing pathogenic Staphylococcus and Streptococcus. Bile Acid Metabolism Reprogramming: WJPS induced a shift in intestinal bile acid profiles, characterized by a decrease in pro-inflammatory taurocholic acid and increased in lithocholic acid—a key agonist of the farnesoid X receptor (FXR)(P<0.05). Concomitantly, colon tissues exhibited upregulation of FXR signaling and suppression of CYP7A1(P<0.05), linking microbiome-derived bile acid metabolites to metabolic regulation. Inflammation Resolution: the formulation attenuated pro-inflammatory cascades, evidenced by a reduction in IL-17A and downregulation of IL-1β(P<0.01), while preserving anti-inflammatory IL-10 homeostasis.ConclusionsThese findings establish WJPS as a multi-target phytogenic modulator that the relative abundance of beneficial bacteria such as Ruminococcus and modulates the relative levels of compounds like glycochenodeoxycholic acid and taurodeoxycholic acid, thereby improving gut health, bile acid signaling, and immunometabolic regulation to enhance ruminant health and productivity. These results provide a translational framework for developing herbal-based feed additives in sustainable livestock production, offering a promising alternative to antimicrobial growth promoters.